The Role of the Bible in Daily Life - Stanko Jambrek; Ljubinka Jambrek (Kairos (English Ed.))
This text is a discussion about the role of the Bible in the daily life of Christians, especially in the process of making decisions. It offers answers to the question: Why is it necessary for a Christian to know God’s Word and to do God’s will? It also looks at the central role of the Bible, not only as the direct Word of God, but also as a historical guide that effectively and powerfully presents the history of the decisions made by individuals and nations regarding God’s will. In the central part of the discussion, along with a biblical explanation of the power of God’s Word and its necessity for Christian living, answers are offered regarding the question as to what God’s will is, shortly explaining what it means to do God’s will in our daily lives, especially in the process of making decisions. In the third part, several steps are suggested regarding the application of the Bible in the process of making decisions.